HUBUNGAN KADAR TROPONIN I DENGAN NILAI MEAN PLATELET VOLUME (MPV) DAN NILAI PLATELET LARGE CELL RATIO (P-LCR) PADA PASIEN SINDROM KORONER AKUT - Kanaya Aulia Masardi; Evy Diah Woelansari; Wisnu Istanto; Suliati Suliati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Acute coronary syndrome (ACS) is a cardiovascular emergency caused by a sudden reduction in myocardial blood flow due to coronary artery obstruction, resulting in myocardial injury. Cardiac Troponin I is a specific biomarker of myocardial damage, whereas Mean Platelet Volume (MPV) and Platelet Large Cell Ratio (P-LCR) are indicators of platelet activity associated with atherothrombotic processes. This study aimed to analyze the relationship between Troponin I levels and MPV and P-LCR values in patients with ACS at Haji Regional General Hospital, East Java Province. An analytical observational study with a cross-sectional design was conducted from January to February 2026. A total of 30 patients diagnosed with ACS were selected using purposive sampling. Troponin I levels were measured using the Fluorescence Immunoassay method, while MPV and P-LCR were assessed using fluorescence flow cytometry. Data were analyzed using Spearman correlation analysis. The results showed that the mean Troponin I level was 2.49 ng/mL, the mean MPV was 10.29 fL, and the mean P-LCR was 26.63%. Spearman analysis demonstrated a significant positive correlation between Troponin I and MPV (p=0.047; r=0.365) as well as between Troponin I and P-LCR (p=0.039; r=0.380). It can be concluded that increased Troponin I levels are associated with elevated platelet activity parameters, indicating that MPV and P-LCR may serve as supportive hematological markers in the evaluation of patients with acute coronary syndrome. ABSTRAK Sindrom koroner akut (SKA) merupakan kegawatdaruratan kardiovaskular yang disebabkan oleh penurunan aliran darah ke miokard akibat penyumbatan arteri koroner dan berpotensi menimbulkan kerusakan jaringan jantung. Troponin I dikenal sebagai biomarker spesifik cedera miokard, sedangkan Mean Platelet Volume (MPV) dan Platelet Large Cell Ratio (P-LCR) merupakan indikator aktivitas trombosit yang berperan dalam proses aterotrombosis. Penelitian ini bertujuan menganalisis hubungan kadar Troponin I dengan nilai MPV dan P-LCR pada pasien SKA di RSUD Haji Provinsi Jawa Timur. Penelitian menggunakan desain observasional analitik dengan pendekatan cross-sectional yang dilaksanakan pada Januari–Februari 2026. Sebanyak 30 pasien SKA dipilih menggunakan teknik purposive sampling. Pemeriksaan Troponin I dilakukan dengan metode Fluorescence Immunoassay, sedangkan MPV dan P-LCR diperiksa menggunakan metode fluorescence flow cytometry. Analisis hubungan antarvariabel dilakukan menggunakan uji korelasi Spearman. Hasil penelitian menunjukkan rata-rata kadar Troponin I sebesar 2,49 ng/mL, MPV sebesar 10,29 fL, dan P-LCR sebesar 26,63%. Uji Spearman menunjukkan terdapat hubungan positif yang bermakna antara kadar Troponin I dengan MPV (p=0,047; r=0,365) serta antara kadar Troponin I dengan P-LCR (p=0,039; r=0,380). Disimpulkan bahwa peningkatan kadar Troponin I berkaitan dengan peningkatan parameter aktivitas trombosit, sehingga MPV dan P-LCR berpotensi menjadi parameter hematologi pendukung dalam evaluasi kondisi pasien sindrom koroner akut.